A method to assess obstetric outcomes using the 10-Group Classification System: a quantitative descriptive study. Issue 7 (12th July 2017) - Rossen, Janne; Lucovnik, Miha; Eggebø, Torbjørn Moe; Tul, Natasa; Murphy, Martina; Vistad, Ingvild; Robson, Michael
Abstract : Objectives: Internationally, the 10-Group Classification System (TGCS) has been used to report caesarean section rates, but analysis of other outcomes is also recommended. We now aim to present the TGCS as a method to assess outcomes of labour and delivery using routine collection of perinatal information. Design: This research is a methodological study to describe the use of the TGCS. Setting: Stavanger University Hospital (SUH), Norway, National Maternity Hospital Dublin, Ireland and Slovenian National Perinatal Database (SLO), Slovenia. Participants: 9848 women from SUH, Norway, 9250 women from National Maternity Hospital Dublin, Ireland and 106 167 women, from SLO, Slovenia. Main outcome measures: All women were classified according to the TGCS within which caesarean section, oxytocin augmentation, epidural analgesia, operative vaginal deliveries, episiotomy, sphincter rupture, postpartum haemorrhage, blood transfusion, maternal age >35 years, body mass index >30, Apgar score, umbilical cord pH, hypoxic–ischaemic encephalopathy, antepartum and perinatal deaths were incorporated. Results: There were significant differences in the sizes of the groups of women and the incidences of events and outcomes within the TGCS between the three perinatal databases. Conclusions: The TGCS is a standardised objective classification system where events and outcomes of labour and delivery can be incorporated. Obstetric core events and outcomes should be agreed and defined to set standards of care. This method provides continuous and available observations from delivery wards, possibly used for further interpretation, questions and international comparisons. The definition of quality may vary in different units and can only be ascertained when all the necessary information is available and considered together.